PENGARUH TEKNOLOGI DALAM MENINGKATKAN DUNIA PENDIDIKAN - Intan Dwi Rahayu; Septiana Vratitiwi; Yola Melshandika; Titik Hardewiyani; Ramadhani Ramadhani (STKIP Pesisir Selatan, 2022)
The development of technology in the world of education has produced many new innovations to support the learning process. One of them is the increasing number of variations of learning media thanks to increasingly rapid technological developments. In the world of education, a shift has been felt, and even a fundamental change at the level of philosophy, direction and purpose. It is no exaggeration to say that scientific progress was triggered by the birth of computer technology. One of the most prominent characteristics of this era is the increasingly interconnected world of science, so that the relationship between them becomes faster. In the context of the use of information and communication technology in the world of education, it has been proven that the